PERANCANGAN ALAT UJI TARIK MORTAR MENGGUNAKAN TENAGA PENGGERAK MOTOR LISTRIK - Sarito Sarito; Muhtarom Riyadi; Handi Sudardja (Jurnal Poli-Teknologi, 2018)
ABSTRACTMechanic characteristics of hard mortar are: compressive strength, flexural strength, tensile strength, and adhesion power. In the meantime, at Building Material Laboratory of Civil Engineering, State Polytechnic of Jakarta, test of tensile strength and adhesion power of mortar cannot be conducted because of the absence of the test equipment.This research aims to provide electric motor-powered equipment for tensile strength test of mortar in order to complete the equipment at Building Material Laboratory of Civil Engineering, State Polytechnic of Jakarta. The particular aim of the research is to make prototype of mortar tensile strength test equipment.In this research a prototype of motor-powered mortar tensile strength test equipment and the specimens, to test the performance of the equipment, were prepared. By examining the obstacles and shortcomings, this equipment is a development of the previous research by Muhtarom Riyadi and the team, 2015. The specimens, as the sample to test the equipment, were prepared by the ratio of one part of cement and three part of fine aggregate, with the total number of the specimens of 50 pieces.By analyzing the result of observation in trial period, the equipment could function as it should be. The magnitude of maximum tensile strength that causes the mortar specimens to break depends on the quality, age, and tensile area of mortar, which magnitude can be observed in manometer or scale with the unit of kilogram.Keywords: equipment, tensile, mortar, electric motorABSTRAKSifat mekanis mortar keras antara lain kuat tekan, kuat lentur, kuat tarik dan daya lekat. Sementara ini di Laboratorium bahan bangunan Jurusan Teknik Sipil Politeknik Negeri Jakarta untuk uji kuat tarik dan daya lekat mortar belum bisa dilaksanakan karena belum adanya peralatan untuk melakukan pengujian.Penelitian ini bertujuan untuk membuat alat uji tarik mortar menggunakan tenaga penggerak motor listrik guna melengkapi peralatan yang diperlukan di Laboratorium bahan bangunan Jurusan Teknik Sipil Politeknik Negeri Jakarta. Target khusus yang ingin dicapai adalah membuat prototype alat uji tarik mortar.Dalam penelitian ini akan dibuat prototipe alat uji tarik mortar menggunakan tenaga motor listrik dan cetakan benda ujinya, sekaligus untuk menguji kinerjanya. Alat ini merupakan pengembangan oleh peneliti yang terdahulu Muhtarom Riyadi dan anggotanya, 2015), dengan mencermati kendala dan kekurangannya maka penelitian ini merupakan penyempurnaan penelitian sebelumnya Sebagai sampelnya dibuat benda uji tarik mortar dengan perbandingan 1 bagian semen berbanding 3 bagian pasir, sedangkan jumlah benda uji dibuat sebanyak 50 buah.Hasil pengamatan selama uji coba maka alat alat uji tarik mortar menggunakan tenaga penggerak motor listrik dapat berfungsi sebagaimana mestinya. Besarnya gaya tarik maksimum yang menjadikan benda uji tarik mortar putus tergantung dari mutu mortar, umur serta luas penampang tarik yang nilainya dapat diamatai pada manometer atau timbangan berat dengan satuan kilogramKata kunci : Alat, uji, tarik, mortar, motor listrik